Molecular effects of the myosin activator omecamtiv mecarbil on contractile properties of skinned myocardium lacking cardiac myosin binding protein-C. (August 2015) - Mamidi, Ranganath; Gresham, Kenneth S.; Li, Amy; dos Remedios, Cristobal G.; Stelzer, Julian E.
Abstract: Decreased expression of cardiac myosin binding protein-C (cMyBP-C) in the myocardium is thought to be a contributing factor to hypertrophic cardiomyopathy in humans, and the initial molecular defect is likely abnormal cross-bridge (XB) function which leads to impaired force generation, decreased contractile performance, and hypertrophy in vivo . The myosin activator omecamtiv mecarbil (OM) is a pharmacological drug that specifically targets the myosin XB and recent evidence suggests that OM induces a significant decrease in the in vivo motility velocity and an increase in the XB duty cycle. Thus, the molecular effects of OM maybe beneficial in improving contractile function in skinned myocardium lacking cMyBP-C because absence of cMyBP-C in the sarcomere accelerates XB kinetics and enhances XB turnover rate, which presumably reduces contractile efficiency. Therefore, parameters of XB function were measured in skinned myocardium lacking cMyBP-C prior to and following OM incubation. We measured k tr, the rate of force redevelopment as an index of XB transition from both the weakly- to strongly-bound state and from the strongly- to weakly-bound states and performed stretch activation experiments to measure the rates of XB detachment ( k rel ) and XB recruitment ( k df ) in detergent-skinned ventricular preparations isolated from hearts of wild-type (WT) and cMyBP-C knockout (KO) mice. Samples from donor human hearts were also used to assess the effects of OM in cardiac muscle expressing a slow β-myosin heavy chain (β-MHC). Incubation of skinned myocardium with OM produced large enhancements in steady-state force generation which were most pronounced at low levels of [Ca 2 + ] activations, suggesting that OM cooperatively recruits additional XB's into force generating states. Despite a large increase in steady-state force generation following OM incubation, parallel accelerations in XB kinetics as measured by k tr were not observed, and there was a significant OM-induced decrease in k rel which was more pronounced in the KO skinned myocardium compared to WT skinned myocardium (58% in WT vs. 76% in KO at pCa 6.1), such that baseline differences in k rel between KO and WT skinned myocardium were no longer apparent following OM-incubation. A significant decrease in the k df was also observed following OM incubation in all groups, which may be related to the increase in the number of cooperatively recruited XB's at low Ca 2 + -activations which slows the overall rate of force generation. Our results indicate that OM may be a useful pharmacological approach to normalize hypercontractile XB kinetics in myocardium with decreased cMyBP-C expression due to its molecular effects on XB behavior. Highlights: Omecamtiv mecarbil (OM) is a novel drug that targets the cardiac XB cycle. OM enhances force generation in skinned myocardium but slows XB kinetics. The effects of OM on XB behavior were most pronounced at low Ca 2 + -activation. OM significantly slowed rates of XB detachment in cMyBP-C -/- skinned myocardium. OM can ameliorate contractile dysfunction due to decreased cMyBP-C expression.